Computer Tool for Automatically Generated 3D Illustration in Real Time from Archaeological Scanned Pieces - Luis López; Germán Arroyo; Domingo Martín (Virtual Archaeology Review)
The graphical documentation process of archaeological pieces requires the active involvement of a professional artist to recreate beautiful illustrations using a wide variety of expressive techniques. Frequently, the artist’s work is limited by the inconvenience of working only with the photographs of the pieces he is going to illustrate. This paper presents a software tool that allows the easy generation of illustrations in real time from 3D scanned models. The developed interface allows the user to simulate very elaborate artistic styles through the creation of diagrams by using the available virtual lights. The software processes the diagrams to render an illustration from any given angle or position. Among the available virtual lights, there are well known techniques as silhouettes enhancement, hatching or toon shading.